Federalismo fiscal e tendência a crises fiscais nos estados brasileiros - Medeiros, Antônio Paulo Vogel de (2023)
Brazilian federalism is crucial to explaining how states reached critical fiscal situations over the last thirty years. The 1988 Federal Constitution gave autonomy to states and municipalities and the financial means necessary to exercise their competencies. However, what is perceived over time is that they recurrently enter into crisis and resort to the help of the Union. In this context, the general objective of this work is to analyze whether the Fiscal Recovery Regime (Complementary Law 159 of 2017) can change the tendency to the crisis of the states within the scope of fiscal federalism in Brazil. The specific objectives are to explore the relationship between fiscal federalism and state crises, analyze case studies of the implementation of this regime, and discuss whether it will be enough to solve these issues. A qualitative approach to investigation and analysis was made through a descriptive research methodology, encompassing bibliographical research, semi-structured interviews, case studies, and documental content analysis. We identified two primary causes for the recurrence of subnational fiscal crises: the difficulty of reaching a consensus among local political and economic elites and the perception of moral hazard in the federative relationship. This situation could have changed in 2017 with the creation of the Tax Recovery Regime. However, we concluded that this did not occur and that this regime can reinforce the moral hazard. To a certain extent, the program helps form consensus but lacks more consistent elements. The country must face the debate on adjusting the federative system to make autonomy compatible with collaboration, cooperation, and regional solidarity among its states. It must also redefine the responsibilities of the heads of all local powers and provide appropriate tools for state managers to address fiscal crises without the help of the Union.